Implementation of Data Envelopment Analysis (DEA) on Measuring the Efficiency of Gas Station Services - Sindhu Priyo Windoko; Dahniar Nur Amalina; Atika Sanjani Ramadina; Syarifa Hanoum (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
Along with the increasing number of transportation vehicles in Indonesia, the growth of the gas station business is also increasing from year to year. This requires companies in the oil and gas industry to improve their performance, and gas stations must have the right strategy to improve efficiency. Measurement of efficiency and productivity is one of the first steps that must be taken by a gas station operation to improve performance. This research analyzes the performance differences in each gas station with the Data Envelopment Analysis (DEA) approach, where DEA is a linear programming model based on measuring the relative efficiency of a unit using many inputs and many outputs. This study aims to identify input and output factors that affect the efficiency level of gas stations, determine the work efficiency of each gas station in carrying out the service process to consumers, and determine the improvement planning strategy for inefficient gas stations